(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to revealing the role of the factor of tolerance in the media environment. The article reveals ethical, cognitive, humanistic, axiological, social aspects of tolerance. The authors of the article pay attention to the cultural, communicative potential of the principle of tolerance in the media space. For the media environment, tolerance is important as a condition for intercultural communication. Norms of tolerant behavior and interaction in the media reveal the value and semantic nature of relation in society, the way to develop moral, cognitive, aesthetic values. Discourse of tolerance affects the nature and results of social, cultural activities of a person. The discourse on tolerance in the context of a social, cultural and «methodological» position is viewed primarily from the standpoint of the priority of the value system. The article defines the variety of factors and criteria for tolerant attitude and behavior in the media environment, as well as the conditions for the development of the practice of tolerance in the modern society. Key words: tolerance, Discourse of tolerance, morality, values, culture, civilization, society, media, communication, personality, cognitive, aesthetic, globalization, media culture.